Capability of X-ray diffraction for the study of microstructure of metastable thin films - David Rafaja; Christina Wüstefeld; Milan Dopita; Mykhaylo Motylenko; Carsten Baehtz (IUCrJ, 2014)
Metastable phases are often used to design materials with outstanding properties, which cannot be achieved with thermodynamically stable compounds. In many cases, the metastable phases are employed as precursors for controlled formation of nanocomposites. This contribution shows how the microstructure of crystalline metastable phases and the formation of nanocomposites can be concluded from X-ray diffraction experiments by taking advantage of the high sensitivity of X-ray diffraction to macroscopic and microscopic lattice deformations and to the dependence of the lattice deformations on the crystallographic direction. The lattice deformations were determined from the positions and from the widths of the diffraction lines, the dependence of the lattice deformations on the crystallographic direction from the anisotropy of the line shift and the line broadening. As an example of the metastable system, the supersaturated solid solution of titanium nitride and aluminium nitride was investigated, which was prepared in the form of thin films by using cathodic arc evaporation of titanium and aluminium in a nitrogen atmosphere. The microstructure of the (Ti,Al)N samples under study was tailored by modifying the [Al]/[Ti] ratio in the thin films and the surface mobility of the deposited species.